PENGARUH MODEL STUDENT TEAMS-ACHIEVEMENT DIVISIONS (STAD) BERBANTUAN MEDIA MIND MAPPING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Jumeiti Tiku Ningsih; Kadek Dewi Wahyuni Andari (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2020)
This research aims to determine the effect by application Student Teams-Achievement Divisions (STAD) type cooperative learning models assisted by Mind Mapping media on the critical thinking skills of Grade IV SD Citra Tarakan students. This research is a quantitative type of quasi-experimental research. This research was conducted in January-February 2020. With a population of fourth grade students at Citra Bangsa Tarakan Elementary School and the sample consisted of one class, namely class IV A which was given treatment. The technique in taking the sample used is Purposive Sampling. The research data were processed with SPSS V.21 for Windows Software. The results of this study indicate that there is an influence on the application of Student Teams-Achievement Divisions (STAD) type cooperative learning models assisted by Mind Mapping media on students' critical thinking abilities. This study shows that the correlation results obtained that the effect of the learning model is very strong with the results of the correlation coefficient of 0.888 and the coefficient of determination of 0.789 or 78.9% and the submission of the hypothesis obtained tcount of 8.638 at a significant level α = 0.05 with df = 20 obtained table of 2,085 means tcount ttable. Keywords: Cooperative learning model type Student Teams-Achievement Divisions (STAD), Critical Thinking Ability,Media Mind Mapping